Quality and Antioxidant Activity of Scrub Bath Soap with Addition of Eucheuma spinosum Algae Powder - Firdayanti Paputungan; Lidya Irma Momuat; Edi Suryanto (Sam Ratulangi University, 2023)
A study was conducted to evaluate the quality and antioxidant activity of solid body soap with the addition of Eucheuma spinosum powder as a scrub. Soap was made by the saponification method between oil (a mixture of olive oil (44%), coconut (24%), and palm (32%)) with NaOH. This study consisted of 4 treatments: (1) without adding algae powder (control) with cold process (TC), (2) adding algae powder with cold process (SC), (3) without adding algae powder (control) with hot process (TH), and (4) the addition of algae powder with a hot process (SH). Soap quality was evaluated using the Indonesian National Standard (SNI) 3532:2021 method, and antioxidant activity using the DPPH method. Parameters tested consisted of pH, total fat, water content, matter insoluble in ethanol, free fatty acids, chlorides, non-saponifiable fats, and the percentage of DPPH inhibition. The results showed that the quality of scrub soap complied with SNI for parameters of pH, content of water, matter insoluble in ethanol and chloride; and did not meet SNI for parameters of total fat, content of free fatty acid and unsaponifiable fat. The percentage of DPPH inhibition of each bath soap at a concentration of 150 µg/mL soap solution was 58.97% TC, 76.76% SC, 56.11% TH and 70.13% SH. Scrub soap with the addition of algae powder had higher antioxidant activity than without the addition of algae powder, both in cold and hot processes. Keywords: Antioxidant; Eucheuma spinosum; scrub bath soap; SNI